How fisheries impact behavioural evolution in Atlantic Cod.
As seen in other animal species, fish individuals tend to react differently to a new situation. In the case of human harvest, the boldest and more active individuals tend to be more likely caught, leaving only the fearful and cautious ones to breed. But does it mean that future generations of fish will become harder to catch? This is one of the questions the BE-FISH project tried to answer.